Associations Between Complementary Feeding Approach, Dietary Intake, and Growth: A Secondary Analysis of the Maternal and Infant Nutrition Trial - Kinzie L. Matzeller; Mikayla L. Hernandez; Gabrielle N.E. Glime; Claudia A. Schaefer; Edward L. Melanson; Daniel N. Frank; Audrey E. Hendricks; Nancy F. Krebs; Minghua Tang (Journal of the Academy of Nutrition and Dietetics, 2026)

Development of a remote sensing algorithm to retrieve chromophoric dissolved organic matter in the Pearl River Estuary - F. Liu; S. Tang (International Journal of Remote Sensing, 2026)

Predictors of bisphenol A exposure in pregnant women of the Barwon Infant Study - Eva J. Sugeng; Sarah Thomson; James Hedley; Martin O’Hely; Christos Symeonides; Samantha L. Dawson; Luba Sominsky; Mimi L.K. Tang; Richard Saffery; Kristie Thompson; Jochen F. Mueller; Anne-Louise Ponsonby (Toxicology Letters, 2026)

Periodic seismic velocity variations in shallow marine sediments using decommissioned fiber-optic cable - Zhenghong Song; Xiangfang Zeng; Herbert F. Wang; He Tang; Sidao Ni; Jiangcun Zhou; Ruyu Yan; Qingwen Liu; Tengfei Xu (Earth and Planetary Science Letters, 2026)

Tailored multifunctional passivation enables efficient and stable flexible perovskite solar cells - Xiaodan Tang; Hongbo Xue; Chenglin Yang; Yafeng Xu; Bo Li; Miao Li; Yuanyuan Zhou; Lulu Jiang; Tuo Liu; Omar F. Mohammed; Xiaopeng Zheng (Chemical Engineering Journal, 2026)

Multi‐Model Ensembles in Ecosystem Modeling: Challenges and Best Practices for Decision‐Making - Kaiyu Guan; Rongzhu Qin; Zewei Ma; Lei Zhao; Licheng Liu; Sheng Wang; Trevor F. Keenan; Mengqi Jia; Debjani Sihi; Eric Potash; Senthold Asseng; Jingyun Tang; et al. (Global Change Biology, 2026)
Ecosystem models are increasingly central to the decision‐making for environmental policy, conservation planning, and climate‐related investments. Yet, the growing reliance on Multi‐Model Ensembles (MMEs) of ecosystem models by practitioners and policymakers, sometimes under tight timelines and imperfect information, has frequently outpaced the scientific rigor required to ensure ensemble reliability. Here, MMEs refer to approaches that combine targeted predictions from multiple models with the expectation of improving robustness and quantifying predictive uncertainty. Poorly designed MMEs may create a false sense of confidence and lead to suboptimal policy and market decisions. This perspective argues that robust decision‐making‐relevant MMEs must be grounded on two pillars: (1) rigorous Model Intercomparison Projects (MIPs), which identify inter‐model agreement and disagreement, characterize model uncertainties, and evaluate robustness with observationally based benchmarks—MIPs' diagnostic evaluation is so critical that it must be needed to drive MME's decision in model selection and weighting, especially when only a limited number of models available; and (2) co‐design by both stakeholders and scientists to ensure that scenarios, metrics and uncertainty requirements provide decision‐relevant information. Building upon the past success and lessons from the existing MIPs‐MMEs efforts (e.g., climate/Earth system/crop), we derived the theoretical basis for MMEs, addressed their specific challenges in ecosystem modeling, and highlighted proper consideration of model numbers and diversity, risk of model inter‐dependence, effective calibration of model parameters, possible overdue of some ecosystem model development, critical roles of open benchmark data across a wide range of conditions, and suggested use of Artificial Intelligence to support MIPs‐MMEs. We highlighted the under‐recognized opportunity for MIPs and MMEs to drive scientific progress and innovation through identifying better performing models, systematic benchmarking, feedback loops, and targeted model improvement. By following actionable best practice guidelines, MMEs can evolve from ad hoc aggregation of models into a trusted backbone of environmental policy and decision‐making.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Rare earth element fractionation in subtropical FeMn nodule-rich red soils: Insights into pedogenic processes and redox dynamics - Xiaoquan Qin; Ning Tang; Damien Guinoiseau; Chengshuai Liu; Marc F. Benedetti; Zongling Ren (Geoderma Regional, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Magmatic-hydrothermal evolution and Li mineralization recorded by correlated crystal chemical zoning of spodumene and muscovite in Lijiagou pegmatites of the Songpan-Garze fold belt, eastern Tibet - Xue Lu; Guangchun Fei; Julian F Menuge; Tianrui Li; Hu Yun; Huipai Zhu; Hua Tan; Yunhua Cai; Guibing Yang; Wenchun Tang; Xi Chen (Mineralium Deposita, 2026)

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

Three-dimensional dust distribution and transport over the northern hemisphere dust belt: Insights from lidar observations - Ruiqi Tan; Tianhe Wang; Ying Han; Jingtao Li; Jingyi Tang; Sichen Wang; Ali Mamtimin; Fan Yang; Chenglong Zhou; Bakhriddin E. Nishonov; Mansur O. Amonov; Sabur F. Abdullaev (Atmospheric Research, 2026)

A stimuli-responsive polymeric ferroptosis drug delivery system for treatment of liver metastases - Deqiang Deng; Muyang Yang; Zhen Zeng; Tianbing Xu; Yuanyuan Geng; Weicheng Tang; Yao Sun; Jonathan F. Lovell; Lisen Lu; Mingxin Zhu; Honglin Jin (Chemical Engineering Journal, 2026)

Household air pollution exposure is associated with perturbations in metabolic pathways in human milk: An observational untargeted metabolomics analysis from Guatemala - Jada Hoyle-Gardner; Ziyin Tang; Donghai Liang; Anaite Diaz-Artiga; Ajay Pillarisetti; Luke Naeher; Kasthuri Sivalogan; Erick Mollinedo; Jiantong Wang; Thomas F. Clasen; Lisa M. Thompson; Sheela S. Sinharoy (Environmental Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of selected food-compatible printing materials on product properties towards 3D binder jetting - Dang Chung Nguyen; Rico F. Tabor; Yunlong Tang; Louise Bennett; Shahnaz Mansouri (Journal of Food Engineering, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The construction of investor-subjects in a housing-led growth society: the case of Hong Kong - Gary Tang; Francis L. F. Lee; Chung-Kin Tsang (The Social Science Journal, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Wall effects on fluid-structure interaction of tandem flapping foils operating in energy extraction mode - F. Zhao; Z. He; Z. Wang; M.N. Mumtaz Qadri; A. Munir; Y. Dong; H. Tang (Ocean Engineering, 2025)

Urban organic manure application enhances antibiotic resistance gene diversity and potential human pathogen abundance in invasive giant African snails - Zhonghui Tang; Yiyue Zhang; Huayuan Shangguan; An Xie; Xueli Xu; Yong Jiang; Martin F. Breed; Xin Sun (Journal of Environmental Sciences, 2025)

An integrated meta-omics approach for identifying candidate organic micropollutant degraders in complex microbial communities - Tal Elad; Kai Tang; Michaël Pierrelée; Marlene Mark Jensen; Mikkel Bentzon-Tilia; Barth F. Smets; Arnaud Dechesne; Borja Valverde-Pérez (Water Research, 2025)

Comparing continuous-corn and soybean-corn rotation cropping systems in the U.S. central Midwest: Trade-offs among crop yield, nutrient losses, and change in soil organic carbon - Ziyi Li; Kaiyu Guan; Wang Zhou; Bin Peng; Emerson D. Nafziger; Robert F. Grant; Zhenong Jin; Jinyun Tang; Andrew J. Margenot; DoKyoung Lee; Carl J. Bernacchi; Evan H. DeLucia; et al. (Agriculture, Ecosystems & Environment, 2025)

Enhanced electrocatalytic hydrogen evolution over a two-dimensional Ti3C2 MXene/FDU-12 templated-nanoporous NiO-decorated carbon paste electrode - Grandprix T.M. Kadja; Aninda F. Nuraini; Ria S. Rahayu; Agam Pamungkas; Ferry Iskandar; Munawar Khalil; Triati D.K. Wungu; Qingjun Yu; Xiaolong Tang; Honghong Yi; Muhammad H. Mahyuddin; Dewi Agustiningsih (Fuel, 2025)

Children’s home environments as reservoirs of antimicrobial resistance: Divergent urban-rural risks from antibiotic resistance genes and pathogens - Shuang Du; Hao Tang; Zhang Wang; Han Chen; Xinyi Fang; Jin Sun; Zhiping Niu; Yiwei Liu; Yuanzhuo Hu; Wen Su; Zhenhua Zhang; Tippawan Prapamontol; et al. (Journal of Hazardous Materials, 2025)

Characterization of astaxanthin isomers in different types of salmon filets and human plasma after salmon consumption - Peiran Lu; Nichole Reisdorph; Audrey E. Hendricks; Richard Reisdorph; Kevin Quinn; Michael Armstrong; Cole Michel; Katrina A. Doenges; Daniel N. Frank; Wayne W. Campbell; Emily B. Hill; Nancy F. Krebs; et al. (Food Chemistry, 2025)

Adjustment of outdoor thermal environment in a Central Business District with high-reflective material and rooftop greening - G. Huang; H. Tang; X. Li; F. Liu; J. Wang; C. Li (International Journal of Environmental Science and Technology, 2025)

An assessment of maternal concentrations of per- and polyfluoroalkyl substances (PFAS) and trace elements during the second trimester of pregnancy in western Pennsylvania - Natalie F. Price; Alexis Kiyanda; Wan-Yee Tang; Zachary Zimmerman; Janet Catov; Aaron Barchowsky; Aubrey L. Galusha; Kurunthachalam Kannan; Elizabeth J. Mullin; Patrick J. Parsons; Nesta Bortey-Sam; Alison P. Sanders (Environmental Monitoring and Assessment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Homozygous deleterious variants in MYCBPAP induce asthenoteratozoospermia involving abnormal acrosome biogenesis, manchette structure and sperm tail assembly in humans and mice - Yiling Zhou; Chaofeng Tu; Charles Coutton; Jianan Tang; Shixiong Tian; Shuyan Tang; Guillaume Martinez; Dapeng Zhou; Célia Tebbakh; Jiaxiong Wang; Raoudha Zouari; Xuehai Zhou; et al. (Science China Life Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Genomic determinants of biological age estimated by deep learning applied to retinal images - Yu Huang; Mohammad Ghouse Syed; Ruiye Chen; Cong Li; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Shulin Tang; Jing Liu; Shunming Liu; Sundar Srinivasan; et al. (GeroScience, 2025)
With the development of deep learning (DL) techniques, there has been a successful application of this approach to determine biological age from latent information contained in retinal images. Retinal age gap (RAG) defined as the difference between chronological age and predicted retinal age has been established previously to predict the age-related disease. In this study, we performed discovery genome-wide association analysis (GWAS) on the RAG using the 31,271 UK Biobank participants and replicated our findings in 8034 GoDARTS participants. The genetic correlation between RAGs predicted from the two cohorts was 0.67 ( P = 0.021). After meta-analysis, we found 13 RAG loci which might be related to retinal vessel density and other aging processes. The SNP-wide heritability ( h 2 ) of RAG was 0.15. Meanwhile, by performing Mendelian randomization analysis, we found that glycated hemoglobin, inflammation hemocytes, and anemia might be associated with accelerated retinal aging. Our study explored the biological implications and molecular-level mechanism of RAG, which might enable causal inference of the aging process as well as provide potential pharmaceutical intervention targets for further treatment. Graphical Abstract

Making waves: Harnessing stormwater for resilient water supply - A blueprint for vulnerable continental coasts and oceanic islands - Lisitai Yang; Enrique Rodriguez Quinones; Evan B. Yao; Qiufeng Lin; Zepei Tang; Walter F․Silva Araya; Yang Deng (Water Research, 2025)

High light intensity improves yield of specialized metabolites in medicinal cannabis (Cannabis sativa L.), resulting from both higher inflorescence mass and concentrations of metabolites - Wannida Sae-Tang; Ep Heuvelink; Céline C.S. Nicole; Elias Kaiser; Kjell Sneeuw; Mexximiliaan M.S.F. Holweg; Sabrina Carvalho; Iris F. Kappers; Leo F.M. Marcelis (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Submesoscale ocean dynamic process contributions to diurnal subsurface chlorophyll variation along Lagrangian recirculation inside mesoscale eddies: A case study in the Southern Ocean - F. Liu; S. Tang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Detrital zircon REE and tectonic settings - Pei-yuan Hu; Qing-guo Zhai; Peter A. Cawood; Roberto F. Weinberg; Guo-chun Zhao; Ren-jie Zhou; Yue Tang; Yi-ming Liu (Lithos, 2024)

Biodegradation of bisphenol-A in water using a novel strain of Xenophilus sp. embedded onto biochar: Elucidating the influencing factors and degradation pathway - Kaili Xu; Yimeng Li; Qian Li; Guorong Yi; Runyu Gao; Kuok Ho Daniel Tang; Esmat F. Ali; Peter.S. Hooda; Sabry M. Shaheen; Ronghua Li (Journal of Hazardous Materials, 2024)

The first ensemble of kilometer-scale simulations of a hydrological year over the third pole - Emily Collier; Nikolina Ban; Niklas Richter; Bodo Ahrens; Deliang Chen; Xingchao Chen; Hui-Wen Lai; Ruby Leung; Lu Li; Alzbeta Medvedova; Tinghai Ou; Praveen Kumar Pothapakula; et al. (Climate Dynamics, 2024)
An accurate understanding of the current and future water cycle over the Third Pole is of great societal importance, given the role this region plays as a water tower for densely populated areas downstream. An emerging and promising approach for skillful climate assessments over regions of complex terrain is kilometer-scale climate modeling. As a foundational step towards such simulations over the Third Pole, we present a multi-model and multi-physics ensemble of kilometer-scale regional simulations for the hydrological year of October 2019 to September 2020. The ensemble consists of 13 simulations performed by an international consortium of 10 research groups, configured with a horizontal grid spacing ranging from 2.2 to 4 km covering all of the Third Pole region. These simulations are driven by ERA5 and are part of a Coordinated Regional Climate Downscaling EXperiment Flagship Pilot Study on Convection-Permitting Third Pole. The simulations are compared against available gridded and in-situ observations and remote-sensing data, to assess the performance and spread of the model ensemble compared to the driving reanalysis during the cold and warm seasons. Although ensemble evaluation is hindered by large differences between the gridded precipitation datasets used as a reference over this region, we show that the ensemble improves on many warm-season precipitation metrics compared with ERA5, including most wet-day and hour statistics, and also adds value in the representation of wet spells in both seasons. As such, the ensemble will provide an invaluable resource for future improvements in the process understanding of the hydroclimate of this remote but important region.

Children's exposure to brominated flame retardants in the home: The TESIE study - Kate Hoffman; Xuening Tang; Ellen M. Cooper; Stephanie C. Hammel; Andreas Sjodin; Allison L. Phillips; Thomas F. Webster; Heather M. Stapleton (Environmental Pollution, 2024)

Plant-based milk: unravel the changes of the antioxidant index during processing and storage – a review - S. C. Tong; L. F. Siow; T. K. Tang; Y. Y. Lee (Critical Reviews in Food Science and Nutrition, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Blueprint for the design, construction, and validation of a plastic and phthalate-minimised laboratory - Cassandra Rauert; Xianyu Wang; Nathan Charlton; Chun-Yin Lin; Cheng Tang; Ian Zammit; Ayomi Jayarathne; Christos Symeonides; Emily White; Michael Christensen; Valentina Ponomariova; Jochen F. Mueller; et al. (Journal of Hazardous Materials, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Effects of biochar combined with nitrogen fertilizer on ryegrass remediation of cadmium-contaminated soil - F. Li; H. Liu; H. Zhong; L. Dong; Y. Tang; Y. Ge (International Journal of Environmental Science and Technology, 2024)

A review of sewage sludge dewatering and stabilisation in reed bed system: towards the process-based modelling - Y. Y. Tan; Y. Z. Huong; F. E. Tang; A. Saptoro (International Journal of Environmental Science and Technology, 2024)
The sludge treatment reed bed is a sustainable sewage sludge management technology that offers promising sludge dewatering and stabilisation, due to its low energy and labour requirements, and minimal operating and maintenance costs. Despite numerous existing studies and increasing applications of sludge treatment reed bed in both developed and developing countries, the lack of standard system configurations and operating regimes led to several operational problems, including bed clogging and poor dewatering and mineralisation efficiency. Sludge dewatering and stabilisation in STBRs are complex processes governed by system- and operation-related factors such as the substrate media, macrophytes, loading regime, sludge characteristics, and climate conditions. Rather than the complex experimental study, process-based modelling has become a promising approach to investigating the influence of specific factors on the efficiency of sludge dewatering and stabilisation. This paper presents an overview of the critical system and operating parameters in sludge treatment reed beds and a summary of the interactions between the factors. Then, a framework of process-based modelling is proposed, which provides a useful platform to study the interactions of operating parameters and other factors in the complex processes of sludge dewatering and stabilisation, which supports the system design and optimisation of sludge treatment reed beds.

Aridity creates global thresholds in soil nitrogen retention and availability - Ahmed S. Elrys; Mohamed F. Abo El‐Maati; Xiaoqian Dan; YuHong Wen; Jinxia Mou; Ahmed Elsayed Abdelghany; Yves Uwiragiye; Tang Shuirong; Wu Yanzheng; Lei Meng; JinBo Zhang; Christoph Müller (Global Change Biology, 2024)
Identifying tipping points in the relationship between aridity and gross nitrogen (N) cycling rates could show critical vulnerabilities of terrestrial ecosystems to climate change. Yet, the global pattern of gross N cycling response to aridity across terrestrial ecosystems remains unknown. Here, we collected 14,144 observations from 451 15 N‐labeled studies and used segmented regression to identify the global threshold responses of soil gross N cycling rates and soil process‐related variables to aridity index (AI), which decreases as aridity increases. We found on a global scale that increasing aridity reduced soil gross nitrate consumption but increased soil nitrification capacity, mainly due to reduced soil microbial biomass carbon (MBC) and N (MBN) and increased soil pH. Threshold response of gross N production and retention to aridity was observed across terrestrial ecosystems. In croplands, gross nitrification and extractable nitrate were inhibited with increasing aridity below the threshold AI ~0.8–0.9 due to inhibited ammonia‐oxidizing archaea and bacteria, while the opposite was favored above this threshold. In grasslands, gross N mineralization and immobilization decreased with increasing aridity below the threshold AI ~0.5 due to decreased MBN, but the opposite was true above this threshold. In forests, increased aridity stimulated nitrate immobilization below the threshold AI ~1.0 due to increased soil C/N ratio, but inhibited ammonium immobilization above the threshold AI ~1.3 due to decreased soil total N and increased MBC/MBN ratio. Soil dissimilatory nitrate reduction to ammonium decreased with increasing aridity globally and in forests when the threshold AI ~1.4 was passed. Overall, we suggest that any projected increase in aridity in response to climate change is likely to reduce plant N availability in arid regions while enhancing it in humid regions, affecting the provision of ecosystem services and functions.

Investigating the association between a history of depression and biomarkers of Alzheimer’s disease, cerebrovascular disease, and neurodegeneration in patients with dementia - Patrick Salwierz; Simrika Thapa; Foad Taghdiri; Anna Vasilevskaya; Chloe Anastassiadis; David F. Tang-Wai; Angela C. Golas; M. Carmela Tartaglia (GeroScience, 2023)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Evaluation and identification of chemical migrants leached from baby food pouch packaging - Cheng Tang; María José Gómez Ramos; Amy Heffernan; Sarit Kaserzon; Cassandra Rauert; Chun-Yin Lin; Jochen F. Mueller; Xianyu Wang (Chemosphere, 2023)

Numerical assessment of non-uniform terrain and inhomogeneous wave–current loading effects on the dynamic response of a submerged floating tunnel - Guoji Xu; Xin Chen; Shihao Xue; Jamie F. Townsend; Xuebin Chen; Maolin Tang (Ocean Engineering, 2023)

Seed Endophytes and Their Roles in Host Plant Stress Resistance - Wenqin Mao; Yuanshuang Wu; Fang Li; Wenting Tang; Weijun Gong; Xue Han; James F. White; Xiuling Ji; Haiyan Li (Journal of Soil Science and Plant Nutrition, 2023)

Methanotrophic oxidation of organic micropollutants and nitrogen upcycling in a hybrid membrane biofilm reactor (hMBfR) for simultaneous O2 and CH4 supply - Anders T. Mortensen; Estelle M. Goonesekera; Arnaud Dechesne; Tal Elad; Kai Tang; Henrik R. Andersen; Barth F. Smets; Borja Valverde-Pérez (Water Research, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Volcanic phosphorus supply boosted Mesozoic terrestrial biotas in northern China - Chao Ma; Yanjie Tang; Ross N. Mitchell; Yongfei Li; Shouliang Sun; Jichang Zhu; Stephen F. Foley; Min Wang; Chenyang Ye; Jifeng Ying; Rixiang Zhu (Science Bulletin, 2023)

Intraperitoneal injection of β-glucan during the suckling period improved the intestinal health of newly weaned rabbits by enhancing immune responses - X. Wang; S.S. Wang; F. Yan; W.Q. Yang; G.F. Tang; M.H. Cui; X.R. Xu (Livestock Science, 2023)

Towards Ensemble-Based Kilometer-Scale Climate Simulations over the Third Pole Region - Andreas F. Prein; Nikolina Ban; Tinghai Ou; Jianping Tang; Koichi Sakaguchi; Emily Collier; Sanjay Jayanarayanan; Lu Li; Stefan Sobolowski; Xingchao Chen; Xu Zhou; Hui-Wen Lai; et al. (Climate Dynamics, 2023)

Responses of coastal sediment organic and inorganic carbon to habitat modification across a wide latitudinal range in southeastern China - Yan Hong; Linhai Zhang; Ping Yang; Chuan Tong; Yongxin Lin; Derrick Y. F. Lai; Hong Yang; Yalian Tian; Wanyi Zhu; Kam W. Tang (CATENA, 2023)

Corrigendum to ’Distinct driving mechanisms of non-growing season N2O emissions call for spatial-specific mitigation strategies in the US Midwest’ [Agricultural and Forest Meteorology 324 (2022) 109108] - Yufeng Yang; Licheng Liu; Wang Zhou; Kaiyu Guan; Jinyun Tang; Taegon Kim; Robert F. Grant; Bin Peng; Peng Zhu; Ziyi Li; Timothy J. Griffis; Zhenong Jin (Agricultural and Forest Meteorology, 2023)

Hydrothermal alteration and corresponding reservoir significance of the Permian Emeishan basaltic lavas, west Sichuan, China - Y. B. Sun; Y. F. Zhang; A. H. Xi; Y. Tang; B. J. Zhang; S. Q. Pei; R. R. Li; H. Yin; Q. Zeng; H. Z. Qu; R. J. Zhou (Australian Journal of Earth Sciences, 2023)

Advancing NMR-based metabolomics using complete reduction to amplitude frequency table: Cultivar differentiation of black ripe table olives as a case study - F. Tang; K. Krishnamurthy; J. Janovick; L. Crawford; S. Wang; E. Hatzakis (Food Chemistry, 2023)

Evolution of diagenetic fluids in the deeply buried, upper Ediacaran Dengying Formation, Central Sichuan Basin, China - Y. J. Hu; C. F. Cai; Y. Li; R. Zhou; Y. J. Tang; J. F. Hu; F. C. Lu; P. Sun (Australian Journal of Earth Sciences, 2023)

Integrating oculomics with genomics reveals imaging biomarkers for preventive and personalized prediction of arterial aneurysms - Yu Huang; Cong Li; Danli Shi; Huan Wang; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Yijun Hu; Shulin Tang; Shunming Liu; Songyuan Luo; et al. (EPMA Journal, 2023)
Objective Arterial aneurysms are life-threatening but usually asymptomatic before requiring hospitalization. Oculomics of retinal vascular features (RVFs) extracted from retinal fundus images can reflect systemic vascular properties and therefore were hypothesized to provide valuable information on detecting the risk of aneurysms. By integrating oculomics with genomics, this study aimed to (i) identify predictive RVFs as imaging biomarkers for aneurysms and (ii) evaluate the value of these RVFs in supporting early detection of aneurysms in the context of predictive, preventive and personalized medicine (PPPM). Methods This study involved 51,597 UK Biobank participants who had retinal images available to extract oculomics of RVFs. Phenome-wide association analyses (PheWASs) were conducted to identify RVFs associated with the genetic risks of the main types of aneurysms, including abdominal aortic aneurysm (AAA), thoracic aneurysm (TAA), intracranial aneurysm (ICA) and Marfan syndrome (MFS). An aneurysm-RVF model was then developed to predict future aneurysms. The performance of the model was assessed in both derivation and validation cohorts and was compared with other models employing clinical risk factors. An RVF risk score was derived from our aneurysm-RVF model to identify patients with an increased risk of aneurysms. Results PheWAS identified a total of 32 RVFs that were significantly associated with the genetic risks of aneurysms. Of these, the number of vessels in the optic disc (‘ntreeA’) was associated with both AAA ( β = −0.36, P = 6.75e−10) and ICA ( β = −0.11, P = 5.51e−06). In addition, the mean angles between each artery branch (‘curveangle_mean_a’) were commonly associated with 4 MFS genes ( FBN1 : β = −0.10, P = 1.63e−12; COL16A1 : β = −0.07, P = 3.14e−09; LOC105373592 : β = −0.06, P = 1.89e−05; C8orf81/LOC441376 : β = 0.07, P = 1.02e−05). The developed aneurysm-RVF model showed good discrimination ability in predicting the risks of aneurysms. In the derivation cohort, the C -index of the aneurysm-RVF model was 0.809 [95% CI: 0.780–0.838], which was similar to the clinical risk model (0.806 [0.778–0.834]) but higher than the baseline model (0.739 [0.733–0.746]). Similar performance was observed in the validation cohort, with a C -index of 0.798 (0.727–0.869) for the aneurysm-RVF model, 0.795 (0.718–0.871) for the clinical risk model and 0.719 (0.620–0.816) for the baseline model. An aneurysm risk score was derived from the aneurysm-RVF model for each study participant. The individuals in the upper tertile of the aneurysm risk score had a significantly higher risk of aneurysm compared to those in the lower tertile (hazard ratio = 17.8 [6.5–48.8], P = 1.02e−05). Conclusion We identified a significant association between certain RVFs and the risk of aneurysms and revealed the impressive capability of using RVFs to predict the future risk of aneurysms by a PPPM approach. Our finds have great potential to support not only the predictive diagnosis of aneurysms but also a preventive and more personalized screening plan which may benefit both patients and the healthcare system. Graphical abstract

Petrogenesis of aplites in the Ke'eryin rare metal orefield in the Songpan-Garze Fold Belt, Eastern Tibet: Evidence from mineralogy, geochemistry, geochronology and Hf-Nd isotopes - Guangchun Fei; Tianrui Li; Julian F. Menuge; Ziqi Hui; Yanwei Yuan; Huipai Zhu; Hua Tan; Yunhua Cai; Wenchun Tang; Guibing Yang; Xiaolong Luo; Zhiping Chen; et al. (Lithos, 2023)

Reduction of Aspergillus flavus and aflatoxin on almond kernels using gaseous chlorine dioxide fumigation - Bhargavi Rane; Alison Lacombe; Jiewen Guan; Lillian Lucero; David F. Bridges; Shyam Sablani; Juming Tang; Vivian C.H. Wu (Food Chemistry, 2023)

Continental-scale Atmospheric Impacts of the 2020 Western U.S. Wildfires - I.S. Albores; R.R. Buchholz; I. Ortega; L.K. Emmons; J.W. Hannigan; F. Lacey; G. Pfister; W. Tang; H.M. Worden (Atmospheric Environment, 2023)

From the basics to emerging diagnostic technologies: What is on the horizon for tilapia disease diagnostics? - Ha Thanh Dong; Thawatchai Chaijarasphong; Andrew C. Barnes; Jérôme Delamare‐Deboutteville; Peiyu Alison Lee; Saengchan Senapin; Chadag Vishnumurthy Mohan; Kathy F. J. Tang; Sharon E. McGladdery; Melba G. Bondad‐Reantaso (Reviews in Aquaculture, 2023)
Tilapia is an affordable protein source farmed in over 140 countries with the majority of production in low‐ and middle‐income countries. Intensification of tilapia farming has exacerbated losses caused by emerging and re‐emerging infectious diseases. Disease diagnostics play a crucial role in biosecurity and health management to mitigate disease loss and improve animal welfare in aquaculture. Three continuous levels of diagnostics (I, II and III) for aquatic species have been proposed by Food and Agriculture Organization of the United Nations (FAO) and the Network of Aquaculture Centers in Asia and the Pacific (NACA) to promote the integration of basic and advanced methods to achieve accurate and meaningful interpretation of diagnostic results. However, the recent proliferation of cutting‐edge molecular methods applied in the diagnosis of diseases of aquacultured animals has shifted the focus of researchers and users away from basic approaches and toward molecular diagnostics, despite the fact that many diseases can be rapidly diagnosed using inexpensive, simple microscopic examination and that most emerging diseases in aquaculture were discovered by histopathology. This review, therefore, revisits and highlights the importance of the three levels of diagnostics for diseases of tilapia, particularly the frequently overlooked basic procedures (e.g., case history records, gross pathology, presumptive diagnostic methods and histopathology). The review also covers current and emerging molecular diagnostic technologies for tilapia pathogens including polymerase chain reaction methods (conventional, quantitative, digital), isothermal amplification methods Loop‐mediated Isothermal Amplification (LAMP), recombinase polymerase amplification (RPA), clustered regularly interspaced short palindromic repeats (CRISPR)‐based detection, lateral flow immunoassays, as well as discussing what is on the horizon for tilapia disease diagnostics (next generation sequencing, artificial intelligence, environmental Deoxyribonucleic Acid (DNA) and Ribonucleic Acid (RNA) and point‐of‐care testing) providing a future vision for transferring these technologies to farmers and stakeholders for a sustainable aquatic food system transformation.

Land use and land cover changes in coastal and inland wetlands cause soil carbon and nitrogen loss - Lishan Tan; Zhenming Ge; Yuhuang Ji; Derrick Y. F. Lai; Stijn Temmerman; Shihua Li; Xiuzhen Li; Jianwu Tang (Global Ecology and Biogeography, 2022)
Aim Natural wetlands are widely considered important for mitigation of climate change, but they have been impacted by land use and land cover change (LULCC), often resulting in ecosystem degradation and significant changes in soil carbon (C) and nitrogen (N) dynamics. However, the impact of various LULCC types on wetland soil C and N dynamics remains unclear. Location Global. Time period 1982–2021. Major taxa studied Wetland. Methods We present a global meta‐analysis using a database of 487 sites compiled from the literature, demonstrating the response of soil C and N concentrations and stocks in coastal wetlands, riparian wetlands and peatlands to various types of LULCCs, including agricultural lands, drained wetlands, aquaculture ponds, pastures and constructed wetlands. Results The conversion of coastal wetlands, riparian wetlands and peatlands to most LULCC types decreased the mean soil C and N concentrations and stocks by 17.8 ± 10.3, 25.3 ± 13.4 and 23.2 ± 6.3%, respectively. The loss of wetland soil C owing to LULCC is estimated to cause a potential CO 2 emission of 1.8–22.8 Mg CO 2 equivalent emission/ha/year, except for conversion to constructed wetlands. The soil C and N contents were more sensitive to LULCCs, relative to the stocks. We also found that the patterns of soil C and N variations were closely related to the conversion time since completion of LULCC. After LULCC, the response of soil C and N variables was sensitive to changes in plant biomass, soil water conditions, bulk density, pH and NH 4 + ‐N concentration, with the major controlling factors varying with the conversion age. Main conclusions Our results highlight the important role of LULCC in triggering soil C and N loss in natural wetlands, which enhances the greenhouse effect. As such, our study calls for sustainable land management strategies aiming at wetland conservation as a powerful tool to mitigate climate warming.

Mechanical Properties and Energy Damage Evolution Characteristics of Coal Under Cyclic Loading and Unloading - Z. W. Ding; J. D. Jia; Q. B. Tang; X. F. Li (Rock Mechanics and Rock Engineering, 2022)

Endophytic bacterial community of Stellera chamaejasme L. and its role in improving host plants' competitiveness in grasslands - Yuejuan Jiang; Qiaohong Li; Wenqin Mao; Wengting Tang; James F. White; Haiyan Li (Environmental Microbiology, 2022)
Summary Stellera chamaejasme has become a problematic weed in northern and south‐western grasslands of China. To evaluate a possible role of endophytes in its strong competitive capacity, the endophytic bacterial community of S . chamaejasme was investigated by culture‐dependent and independent methods, and the growth‐promoting traits of some culturable isolates as well as the benefit of endophyte ST3CS3 ( Brevundimonas sp.) on host plants growth were studied. The results showed that 823 OTUs were generated with a 97% similarity level in the culture‐independent study. They were classified into 29 phyla, 61 classes, 147 orders, 237 families and 440 genera. Among them, Pseudomonas and Ralstonia were the most dominant genera in belowground parts (G) (64.25%) and aboveground parts (S) (26.54%) respectively. The diversity and species richness of endophytes in S were significantly higher than that of G ( P t ‐test). Contrary to this, the number of culturable bacteria in S was a little lower than that of G ( P > 0.05, t ‐test). Totally, 176 isolates belonging to 30 morphotypes were obtained in the culture‐dependent study. Among them, Acinetobacter was the most dominant genus in G (51.30%), then followed by Pseudomonas (6.09%) and Brevundimonas (6.09%), while Lysinibacillus (21.31%) was the most dominant genus in S, followed by Pseudomonas (11.48%). Growth‐promoting trait tests indicated that 93.65% of the tested isolates (63) exhibited nitrogen‐fixing, IAA‐synthesizing, phosphorus or potassium solubilizing capacity, in which 77.97% belonged to Proteobacteria, a phylum found to contain more active isolates. Pot experiments demonstrated that endophyte ST3CS3 can significantly improve host plants growth and increase its nitrogen and chlorophyll content ( P t ‐test). Therefore, we suggest that strong competitiveness of S . chamaejasme may in part be due to possession of high ratios of plant growth‐promoting proteobacterial endophytes such as Pseudomonas , Acinetobacter and Brevundimonas .

Calcium Enabled Remote Loading of a Weak Acid Into pH-sensitive Liposomes and Augmented Cytosolic Delivery to Cancer Cells via the Proton Sponge Effect - Mimi M. Yang; Sasi Bhushan Yarragudi; Stephen M. F. Jamieson; Mingtan Tang; William R. Wilson; Zimei Wu (Pharmaceutical Research, 2022)
While delivery of chemotherapeutics to cancer cells by nanomedicines can improve therapeutic outcomes, many fail due to the low drug loading (DL), poor cellular uptake and endosomal entrapment. This study investigated the potential to overcome these limitations using pH-sensitive liposomes (PSL) empowered by the use of calcium acetate. An acidic dinitrobenzamide mustard prodrug SN25860 was used as a model drug, with non pH-sensitive liposomes (NPSL) as a reference. Calcium acetate as a remote loading agent allowed to engineer PSL- and NPSL-SN25860 with DL of > 31.1% (w/w). The IC 50 of PSL-SN25860 was 21- and 141-fold lower than NPSL and free drug, respectively. At 48 h following injection of PSL-SN25860, NPSL-SN25860 and the free drug, drug concentrations in EMT6- nfsB murine breast tumors were 56.3 µg/g, 6.76 µg/g and undetectable (< 0.015 µg/g), respectively (n = 3). Meanwhile, the ex vivo tumor clonogenic assay showed 9.1%, 19.4% and 42.7% cell survival in the respective tumors. Live-cell imaging and co-localization analysis suggested endosomal escape was accomplished by destabilization of PSL followed by release of Ca 2+ in endosomes allowing induction of a proton sponge effect. Subsequent endosomal rupture was observed approximately 30 min following endocytosis of PSL containing Ca 2+ . Additionally, calcium in liposomes promoted internalization of both PSL and NPSL. Taken together, this study demonstrated multifaceted functions of calcium acetate in promoting drug loading into liposomes, cellular uptake, and endosomal escape of PSL for efficient cytoplasmic drug delivery. The results shed light on designing nano-platforms for cytoplasmic delivery of various therapeutics. Graphical abstract

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)

A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)
There is great need for coordination around standards and best practices in neuroscience to support efforts to make neuroscience a data-centric discipline. Major brain initiatives launched around the world are poised to generate huge stores of neuroscience data. At the same time, neuroscience, like many domains in biomedicine, is confronting the issues of transparency, rigor, and reproducibility. Widely used, validated standards and best practices are key to addressing the challenges in both big and small data science, as they are essential for integrating diverse data and for developing a robust, effective, and sustainable infrastructure to support open and reproducible neuroscience. However, developing community standards and gaining their adoption is difficult. The current landscape is characterized both by a lack of robust, validated standards and a plethora of overlapping, underdeveloped, untested and underutilized standards and best practices. The International Neuroinformatics Coordinating Facility (INCF), an independent organization dedicated to promoting data sharing through the coordination of infrastructure and standards, has recently implemented a formal procedure for evaluating and endorsing community standards and best practices in support of the FAIR principles. By formally serving as a standards organization dedicated to open and FAIR neuroscience, INCF helps evaluate, promulgate, and coordinate standards and best practices across neuroscience. Here, we provide an overview of the process and discuss how neuroscience can benefit from having a dedicated standards body.

Numerical and experimental studies of turbulence in vegetated open-channel flows - Xiaochun Tang; Pengzhi Lin; Philip L.-F. Liu; Xiaofeng Zhang (Environmental Fluid Mechanics, 2021)

Taurine Reduces Liver Damage in Non-Alcoholic Fatty Liver Disease Model in Rats by Down-Regulating IL-9 and Tumor Growth Factor TGF-β - Z. Yao; G. Liang; Z. L. Lv; L. C. Lan; F. L. Zhu; Q. Tang; L. Huang; X. Q. Chen; M. X. Yang; Q. W. Shan (Bulletin of Experimental Biology and Medicine, 2021)

Natural infection of covert mortality nodavirus affects Zebrafish ( Danio rerio ) - Chong Wang; Shuang Liu; Kathy F. J. Tang; Qingli Zhang (Journal of Fish Diseases, 2021)
Covert mortality nodavirus (CMNV), a novel aquatic pathogen, causes viral covert mortality disease (VCMD) in shrimps and also known to infect farmed marine fish. To date, there has no report regarding the ability of this virus to infect freshwater fish. In this study, we screened and discovered CMNV‐positive freshwater zebrafish individuals by reverse transcription‐nested PCR (RT‐nPCR). The sequence of CMNV amplicons from zebrafish was found to share 99% identity with RNA‐dependent RNA polymerase (RdRp) gene of the original CMNV isolate. Histopathological examination of the CMNV‐positive zebrafish samples revealed extensive vacuolation and karyopyknosis lesions in the retina of the eye and the midbrain mesencephalon. CMNV‐like virus particles were visualized in these tissues under transmission electron microscope. Different degrees of pathological damages were also found in muscle, gills, thymus and ovarian tissues. Strong positive signals of CMNV probe were observed in these infected tissues by in situ hybridization. Overall, all results indicated that zebrafish, an acknowledged model organism, could be infected naturally by CMNV. Thus, it is needed to pay close attention to the possible interference of CMNV whether in assessment of toxic substances, or in studying the developmental characterization and the nerval function, when zebrafish was used as model animal.

Natural Infection of Covert Mortality Nodavirus in Small Yellow Croaker in Coastal Water - Tingting Xu; Yingxia Li; Xiujuan Shan; Jingwei Hao; Qiang Wu; Kathy F. J. Tang; Qingli Zhang; Cuiluan Yao (Frontiers in Marine Science, 2021)
Covert mortality nodavirus (CMNV) is an alphanodavirus mainly infecting marine shrimp and co-inhabiting organisms in aquaculture ponds. To evaluate the possibility of CMNV prevalence in the wild fish species, epidemiological survey of CMNV infection in Larimichthys polyactis , the dominant species in the Yellow Sea and East China Sea, were conducted in the present study. We performed CMNV RT-LAMP assay in samples of L. polyactis collected in August 2018 and 2019 and found that CMNV prevalence was 18% and 7%, respectively. The nucleotide sequences of both RdRp and capsid protein genes of CMNV from L. polyactis were 99% similar to those of CMNV isolated from shrimp. CMNV-positive L. polyactis exhibited necrosis of cardiac muscle, oocytes loosely arranging, severe cytoplasmic vacuolation of hepatocytes, moderate pyknosis of brain pyramidal cells, degenerate renal tubular cells with ill-defined margins, and declined spleen cells in the histological examination. Moreover, CMNV-positive signals were further observed in pyramidal cells of the brain, the cortical area of the kidney, oocyte growth rings, and in necrotic tissues of cardiac muscle, liver, and spleen in the in situ hybridization assay. The results revealed that CMNV had colonized in the wild populations of L. polyactis and the ecological risk of CMNV spread and epidemic in wild fish in the coastal water was non-negligible.

Taxonomy of the Trichophyton mentagrophytes/T. interdigitale Species Complex Harboring the Highly Virulent, Multiresistant Genotype T. indotineae - Chao Tang; Xue Kong; Sarah A. Ahmed; Rameshwari Thakur; Anuradha Chowdhary; Pietro Nenoff; Silke Uhrlass; Shyam B. Verma; Jacques F. Meis; Hazal Kandemir; Yingqian Kang; G. Sybren de Hoog (Mycopathologia, 2021)
A severe outbreak of highly virulent and multi-resistant dermatophytosis by species in the Trichophyton mentagrophytes / T . interdigitale complex is ongoing in India. The correct identity of the etiologic agent is a much-debated issue. In order to define species limits, a taxonomic study was undertaken combining molecular, morphological, and physiological characteristics as evidence of classification. Molecular characteristics show that T. mentagrophytes s. str . and T. interdigitale s. str . can be distinguished with difficulty from each other, but are unambiguously different from the Indian genotype, T . indotineae by sequences of the HMG gene. The entities were confirmed by multilocus analysis using tanglegrams. Phenotypic characters of morphology and physiology are not diagnostic, but statistically significant differences are observed between the molecular siblings. These properties may be drivers of separate evolutionary trends. Trichophyton mentagrophytes represents the ancestral, homothallic cloud of genotypes with a probable geophilic lifestyle, while T . indotineae and T . interdigitale behave as anthropophilic, clonal offshoots. The origin of T . indotineae , which currently causes a significant public health problem, is zoonotic, and its emergence is likely due to widespread misuse of antifungals.

Comprehensive thermal maturity assessment in shales: a case study on the upper cretaceous Qingshankou formation (Songliao Basin, NE China) - Penglin Zhang; David Misch; Qingtao Meng; Achim Bechtel; Reinhard F. Sachsenhofer; Zhaojun Liu; Fuhong Gao; Fei Hu; Shuaihua Zhang; Baiqiang Tang (International Journal of Earth Sciences, 2021)

Similarities and differences in the sensitivity of soil organic matter (SOM) dynamics to biogeochemical parameters for different vegetation inputs and climates - G. Ceriotti; F. H. M. Tang; F. Maggi (Stochastic Environmental Research and Risk Assessment, 2020)

Application of ornithine-induced regulation in yield formation, grain quality and aroma of fragrant rice - H. W. Luo; P. P. Xing; J. H. Liu; R. F. Lai; L. X. He; T. T. Zhang; X. R. Tang (Cereal Research Communications, 2020)

Genetic determinism of prickles in rose - N. N. Zhou; K. X. Tang; J. Jeauffre; T. Thouroude; D. C. Lopez Arias; F. Foucher; L. Hibrand-Saint Oyant (Theoretical and Applied Genetics, 2020)

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Maternal urinary bisphenol A concentration and thyroid hormone levels of Chinese mothers and newborns by maternal body mass index - Xia Wang; Ning Tang; Shoji F. Nakayama; Pianpian Fan; Zhiwei Liu; Jun Zhang; Fengxiu Ouyang (Environmental Science and Pollution Research, 2020)

Phylogenetic and population genetic analyses reveal three distinct lineages of the invasive brown root-rot pathogen, Phellinus noxius, and bioclimatic modeling predicts differences in associated climate niches - J. E. Stewart; M.-S. Kim; Y. Ota; N. Sahashi; J. W. Hanna; M. Akiba; J. P. Ata; N. Atibalentja; F. Brooks; C.-L. Chung; E. K. Dann; A. Mohd Farid; et al. (European Journal of Plant Pathology, 2020)

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Biomass and pigments production of a newly isolated photosynthetic bacterium Ectothiorhodospira shaposhnikovii P2 from saline wastewater - J. Cai; Y. Guan; F. Li; Y. Zhao; C. Feng; N. Tang (International Journal of Environmental Science and Technology, 2019)

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Characterization, tissue distribution of apela and periprandial, fasting and refeeding changes of apela mRNA in Siberian sturgeon Acipenser baerii - Ni Tang; Jin Hao; Xin Zhang; Yuan B. Wu; Shu Y. Wang; Jin W. Qi; Zhen Z. Tian; Bin Wang; Hu Chen; De F. Chen; Zhi Q. Li (Journal of Fish Biology, 2018)
Apela identified from zebrafish Danio rerio for the first time in 2013 is a novel endogenous peptide ligand for the apelin receptor. To study the role of apela in regulating fish feeding, the complementary (c) DNA sequence of apela of Siberian sturgeon Acipenser baerii was cloned for the first time. The apela cDNA fragment of 836 bp was obtained by cloning. The open reading frame (ORF) of apela was 165 bp encoding a 54 amino acid, including 22 amino acids signal peptide and two proteolytic sites. Phylogenetic tree analysis showed that A. baerii apela was clustered with mammalian and amphibian sequences. A. baerii apela messeger (m)RNA was widely distributed in 11 tissues related to feeding, with high expressions in brain, oesophagus and stomach, especially in the brain. The level of apela mRNA in brain increased significantly after feeding. On the first day of fasting, apela expression in brain was significantly lower than that of the fed group, but after fasting for 3–15 days, the expression of apela in A. baerii brain was significantly higher than that in the fed group. After refeeding apela mRNA expression was obviously reduced. These results suggest that apela plays a bidirectional role in feeding regulation of A. baerii , which may serve as a short‐term satiation factor and a long‐term hunger factor.

Susceptibility profile of echinocandins, azoles and amphotericin B against yeast phase of Talaromyces marneffei isolated from HIV-infected patients in Guangdong, China - H.-L. Lei; L.-H. Li; W.-S. Chen; W.-N. Song; Y. He; F.-Y. Hu; X.-J. Chen; W.-P. Cai; X.-P. Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The peptide lycosin-I attenuates TNF-α-induced inflammation in human umbilical vein endothelial cells via IκB/NF-κB signaling pathway - Xianyao Li; Yaqin Tang; Binbin Ma; Zheng Wang; Jinying Jiang; Shengjie Hou; Shuhang Wang; Jie Zhang; Meichun Deng; Zhigui Duan; Xing Tang; Alex F. Chen; et al. (Inflammation Research, 2018)

Phage Application for the Protection from Acute Hepatopancreatic Necrosis Disease (AHPND) in Penaeus vannamei - Jin Woo Jun; Jee Eun Han; Sib Sankar Giri; Kathy F. J. Tang; Xiaohui Zhou; Luis Fernando Aranguren; Hyoun Joong Kim; Saekil Yun; Cheng Chi; Sang Guen Kim; Se Chang Park (Indian Journal of Microbiology, 2018)

Seasonal Factors Influencing Copepod Abundance in the Maryland Coastal Bays - Efeturi U. Oghenekaro; Paulinus Chigbu; Ozuem F. Oseji; Kam W. Tang (Estuaries and Coasts, 2018)

Microscopy-based high-throughput assays enable multi-parametric analysis to assess adverse effects of nanomaterials in various cell lines - Iris Hansjosten; Juliane Rapp; Luisa Reiner; Ruben Vatter; Susanne Fritsch-Decker; Ravindra Peravali; Taina Palosaari; Elisabeth Joossens; Kirsten Gerloff; Peter Macko; Maurice Whelan; Douglas Gilliland; et al. (Archives of Toxicology, 2018)

The burden and epidemiology of community-acquired central nervous system infections: a multinational study - H. Erdem; A. Inan; E. Guven; S. Hargreaves; L. Larsen; G. Shehata; E. Pernicova; E. Khan; L. Bastakova; S. Namani; A. Harxhi; T. Roganovic; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Molecular characterization of a novel bipartite begomovirus isolated from Lycianthes biflora in China - Y. F. Tang; Z. F. He; J. K. Brown; X. M. She; G. B. Lan (Archives of Virology, 2017)

Identification and expression analysis of terminal deoxynucleotidyl transferase in humphead snapper Lutjanus sanguineus - Y. Huang; J. Cai; J. F. Tang; H. Y. Zhang; Z. W. Wang; J. C. Jian; Z. H. Wu; Y. S. Lu (Journal of Fish Biology, 2017)
A tdt gene was identified successfully from humphead snapper Lutjanus sanguineus , which contained 1710 bp encoding a protein of 463 amino acids. Results of quantitative real‐time polymerase chain reaction ( qRT‐PCR ) indicated that tdt mainly expressed in thymus and head kidney and the transcripts of tdt in these tissues were up‐regulated significantly at 36 and 48 h after Vibrio harveyi infection. Meanwhile Tdt‐producing cells were found in thymus and head kidney.

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Cross‐scale intercomparison of climate change impacts simulated by regional and global hydrological models in eleven large river basins - F. F. Hattermann; V. Krysanova; S. N. Gosling; R. Dankers; P. Daggupati; C. Donnelly; M. Flörke; S. Huang; Y. Motovilov; S. Buda; T. Yang; C. Müller; et al. (Climatic Change, 2017)

Validation of daily increment deposition and early growth of mud carp Cirrhinus molitorella - Y. Huang; F. Chen; W. Tang; Z. Lai; X. Li (Journal of Fish Biology, 2017)
In this study, laboratory reared Cirrhinus molitorella from hatching through to the juvenile stage were used to validate daily increment deposition. Lapilli were suitable for ageing C. molitorella . The slope of the linear relationships between increment counts and age was not significantly different from 1 ( n = 258, P > 0·05), indicating that growth increments are deposited daily. The first increment following the first‐feeding check formed 3 days post hatch (dph). One hundred and twenty‐three juveniles, ranging from 36·4 to 84·7 mm in body length ( L B ), were collected in the Pear River estuary from July to January in both 2014 and 2015 and used to estimate growth rate. The core in the lapillus, consisting of a single primordium, a diffuse area and the first‐feeding band, was followed by 20 narrow and poorly contrasted daily increments. Thereafter, increments were wide and well‐defined, and, finally became less distinct, but still homogenous after c. 53 dph. The mean increment width increased to the 29th increment and stayed relatively constant up to the 35th increment and then, gradually declined to the edge of the otolith. Wild juveniles were aged from 69 to 178 dph and hatched from the 15 February to 2 September. Growth rate was estimated from the adjusted linear regression of L B on age: L B = 4·37 + 0·44 A ( r 2 = 0·60), where A = age. The radius of the core and the regularity and resolution of the increments showed some differences between reared and wild fish. These results are of value for the further study of early life traits and recruitment of C. molitorella .

New insights into the photochemistry of carotenoid spheroidenone in light-harvesting complex 2 from the purple bacterium Rhodobacter sphaeroides - Dariusz M. Niedzwiedzki; Preston L. Dilbeck; Qun Tang; Elizabeth C. Martin; David F. Bocian; C. Neil Hunter; Dewey Holten (Photosynthesis Research, 2017)

Ecosystem fluxes of hydrogen in a mid‐latitude forest driven by soil microorganisms and plants - Laura K. Meredith; Róisín Commane; Trevor F. Keenan; Stephen T. Klosterman; J. William Munger; Pamela H. Templer; Jianwu Tang; Steven C. Wofsy; Ronald G. Prinn (Global Change Biology, 2017)
Molecular hydrogen (H 2 ) is an atmospheric trace gas with a large microbe‐mediated soil sink, yet cycling of this compound throughout ecosystems is poorly understood. Measurements of the sources and sinks of H 2 in various ecosystems are sparse, resulting in large uncertainties in the global H 2 budget. Constraining the H 2 cycle is critical to understanding its role in atmospheric chemistry and climate. We measured H 2 fluxes at high frequency in a temperate mixed deciduous forest for 15 months using a tower‐based flux‐gradient approach to determine both the soil‐atmosphere and the net ecosystem flux of H 2 . We found that Harvard Forest is a net H 2 sink (−1.4 ± 1.1 kg H 2 ha −1 ) with soils as the dominant H 2 sink (−2.0 ± 1.0 kg H 2 ha −1 ) and aboveground canopy emissions as the dominant H 2 source (+0.6 ± 0.8 kg H 2 ha −1 ). Aboveground emissions of H 2 were an unexpected and substantial component of the ecosystem H 2 flux, reducing net ecosystem uptake by 30% of that calculated from soil uptake alone. Soil uptake was highly seasonal (July maximum, February minimum), positively correlated with soil temperature and negatively correlated with environmental variables relevant to diffusion into soils (i.e., soil moisture, snow depth, snow density). Soil microbial H 2 uptake was correlated with rhizosphere respiration rates ( r = 0.8, P 2 metabolism yielded up to 2% of the energy gleaned by microbes from carbon substrate respiration. Here, we elucidate key processes controlling the biosphere–atmosphere exchange of H 2 and raise new questions regarding the role of aboveground biomass as a source of atmospheric H 2 and mechanisms linking soil H 2 and carbon cycling. Results from this study should be incorporated into modeling efforts to predict the response of the H 2 soil sink to changes in anthropogenic H 2 emissions and shifting soil conditions with climate and land‐use change.

A multi-center, controlled, randomized, open-label clinical study of levofloxacin for preventing infection during the perioperative period of ultrasound-guided transrectal prostate biopsy - L.-D. Qiao; S. Chen; X.-F. Wang; W.-M. Yang; Y.-J. Niu; C.-Z. Kong; W. Tang; X.-F. Gao; B.-K. Shi; Y.-Q. Na; X.-D. Zhang; J.-Y. Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Understanding marine dissolved organic matter production: Compositional insights from axenic cultures of Thalassiosira pseudonana - Emily M. Saad; Amelia F. Longo; Luke R. Chambers; Rixiang Huang; Claudia Benitez‐Nelson; Sonya T. Dyhrman; Julia M. Diaz; Yuanzhi Tang; Ellery D. Ingall (Limnology and Oceanography, 2016)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

Molecular cloning and characterization of lymphocyte cell kinase from humphead snapper ( Lutjanus sanguineus ) - Y Huang; J Cai; B Wang; J‐F Tang; J‐C Jian; Z‐H Wu; Z Gan; Y‐S Lu (Journal of Fish Diseases, 2016)
Lymphocyte cell kinase ( LCK ) belongs to the Src family of tyrosine kinases, which involves in the proliferation control of lymphocytes. In this study, we cloned the LCK gene of humphead snapper ( Lutjanus sanguineus ) (designed as Ls LCK ). Sequence analysis showed that the full‐length cDNA of Ls LCK was 2279 bp, contained a 1506‐bp open reading frame ( ORF ), encoding a polypeptide of 501 amino acids. The deduced amino acid possessed the typical structural features of known LCK proteins, including four Src homology ( SH ) domains arranged as the SH 1 domain followed by a regulatory C‐terminal tail ( COOH ‐domain), SH 2 and SH 3 adapter domains and SH 4 domain which required for membrane attachment and CD 4/ CD 8 binding. Fluorescent quantitative real‐time PCR analysis indicated that Ls LCK transcripts were expressed mainly in thymus, spleen and head kidney in healthy fish. Moreover, the mRNA expressions in these tissues were significantly up‐regulated after challenge with Vibrio harveyi . The results of immunohistochemistry showed that Ls LCK protein localized distinctly in cytoplasm of cell in thymus, spleen and head kidney. Taken together, these findings indicated that Ls LCK may play an important role in the immune response of humphead snapper against bacterial infection.

Microseismic Monitoring of Strainburst Activities in Deep Tunnels at the Jinping II Hydropower Station, China - N. W. Xu; T. B. Li; F. Dai; R. Zhang; C. A. Tang; L. X. Tang (Rock Mechanics and Rock Engineering, 2016)

Visual detection technique for efficient screening and isolation of Salmonella based on a novel enrichment assay using chromatography membrane - F. Tang; Y. Xiong; H. Zhang; K. Wu; Y. Xiang; J.-B. Shao; H.-W. Ai; Y.-P. Xiang; X.-L. Zheng; J.-R. Lv; H. Sun; L.-S. Bao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Vertical stratification of moths across elevation and latitude - Louise A. Ashton; Akihiro Nakamura; Yves Basset; Chris J. Burwell; Min Cao; Rodney Eastwood; Erica Odell; Evandro Gama de Oliveira; Karen Hurley; Masatoshi Katabuchi; Sarah Maunsell; James McBroom; et al. (Journal of Biogeography, 2016)
Aim There is little consensus as to whether stratification of arthropods between canopy and understorey in tropical and subtropical forests is commonplace and if the magnitude of stratification changes across different elevations and latitudes. We investigated broad‐scale patterns of vertical stratification of moths collected from extensive cross‐continental fieldwork in a variety of forest types, climates, elevations, latitudes and areas with differing biogeographical history. Location Tropical and subtropical rain forest in eastern Australia; tropical, subtropical and subalpine forest in Yunnan Province, China; and tropical rain forest in Panama, Vietnam, Brunei and Papua New Guinea. Methods Night‐flying moths were trapped from the upper canopy and understorey. We generated a total of 64 data sets to quantify vertical stratification of moths in terms of their species richness, using coverage‐based rarefaction, and assemblage composition, using standardized hierarchical beta diversity. Based on the average temperature lapse rate, we incorporated latitudinal differences into elevation and generated ‘corrected’ elevation for each location, and analysed its relationships with the magnitude of stratification. Results We found consistent differences between canopy and understorey assemblages at almost all rain forest locations across corrected elevational gradients. The magnitude of vertical stratification in species richness did not change with increasing corrected elevation. In contrast, the difference in assemblage composition increased with increasing corrected elevation in the Northern Hemisphere, while the opposite, albeit weak, trend was found in the Southern Hemisphere. Main conclusions Clear vertical stratification was evident in moth assemblages regardless of elevation and latitude. However, the degree to which assemblages are stratified between canopy and understorey is not uniformly related to elevation and latitude. Inconsistencies in the magnitude of vertical stratification between the Northern and Southern Hemisphere, may reflect, on one hand, deep‐time biogeographical differences between the land masses studied and, on the other, place‐to‐place differences in resource availability underpinning the observed moth assemblages.

Contrasting effects of organic amendments on phytoextraction of heavy metals in a contaminated sediment - Chengjun Zhang; Gary J. Clark; Antonio F. Patti; Nanthi Bolan; Miaomiao Cheng; Peter W. G. Sale; Caixian Tang (Plant and Soil, 2015)

A Real-Time Analysis and Feedback System for Quality Control of Dam Foundation Grouting Engineering - D. H. Zhong; F. G. Yan; M. C. Li; C. X. Huang; K. Fan; J. F. Tang (Rock Mechanics and Rock Engineering, 2015)

Direct visualization of the novel pathogen, S piroplasma eriocheiris , in the freshwater crayfish P rocambarus clarkii ( G irard) using fluorescence in situ hybridization - Z F Ding; S Y Xia; H Xue; J Q Tang; Q Ren; W Gu; Q G Meng; W Wang (Journal of Fish Diseases, 2015)
Spiroplasma eriocheiris is the first spiroplasma strain known to be pathogenic to freshwater crustaceans. It has caused considerable economic losses both in the freshwater crayfish P rocambarus clarkii ( G irard) and in some other crustaceans. The monitoring of the pathogen in crustacean populations and study of its behaviour in the laboratory require the development of reliable diagnostic tools. In this article, we improved microscopic identification of S . eriocheiris by combining in situ hybridization with specific fluorescently labelled oligonucleotide probes. The established fluorescence in situ hybridization ( FISH ) allowed simultaneous visualization, identification and localization of S . eriocheiris in the tissues of diseased crayfish P . clarkii and exhibited low background autofluorescence and ideal signal‐to‐noise ratio. With the advantages of better tissue penetration, potentially more specific and stable, we designed three species‐specific oligonucleotide probes utilizing the sequences of 16 S ‐23 S r RNA intergenic spacer regions ( ISR s) of S . eriocheiris . Positive hybridization signals were visualized in haemocytes and connective tissues of hepatopancreas, cardiac muscle and gill from diseased crayfish. This unique distribution pattern matched the pathological changes when diagnosed by H & E staining and indicated that S . eriocheiris probably spread throughout the tissues in P . clarkii by hemokinesis. This assay will facilitate our understanding of the pathogenesis of S . eriocheiris and enhance the early diagnosis of the novel pathogen.

Choline Ameliorates Deficits in Balance Caused by Acute Neonatal Ethanol Exposure - Cynthia F. Bearer; Kristen A. Wellmann; Ningfeng Tang; Min He; Sandra M. Mooney (The Cerebellum, 2015)

Basing RNA-seq explored the regulatory mechanism of the carbohydrate metabolism pathways during chicken male germ cell differentiation - Chao Lian; Qisheng Zuo; Dong Li; Lei Zhang; Mahmoud F. Ahmed; Tianrong Xiao; Beibei Tang; Yingjie Wang; Kai Jin; Yani Zhang; Bichun Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Regulatory mechanism of protein metabolic pathway during the differentiation process of chicken male germ cell - Dong Li; Qisheng Zuo; Chao Lian; Lei Zhang; Qingqing Shi; Zhentao Zhang; Yingjie Wang; Mahmoud F. Ahmed; Beibei Tang; Tianrong Xiao; Yani Zhang; Bichun Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Extended genome sequences of penaeid shrimp infectious myonecrosis virus strains from Brazil and Indonesia - Sidrotun Naim; Kathy F.-J. Tang; May Yang; Donald V. Lightner; Max L. Nibert (Archives of Virology, 2015)

Astrocytic Cx 43 and Cx 40 in the mouse hippocampus during and after pilocarpine-induced status epilepticus - X. L. Wu; Y. C. Tang; Q. Y. Lu; X. L. Xiao; T. B. Song; F. R. Tang (Experimental Brain Research, 2015)

Overexpression of an Aeluropus littoralis Parl. potassium transporter gene, AlHAK1, in cotton enhances potassium uptake and salt tolerance - J. F. Liu; S. L. Zhang; H. L. Tang; L. Z. Wu; L. J. Dong; L. D. Liu; W. L. Che (Euphytica, 2015)

Consequence of altered nitrogen cycles in the coupled human and ecological system under changing climate: The need for long-term and site-based research - Hideaki Shibata; Cristina Branquinho; William H. McDowell; Myron J. Mitchell; Don T. Monteith; Jianwu Tang; Lauri Arvola; Cristina Cruz; Daniela F. Cusack; Lubos Halada; Jiří Kopáček; Cristina Máguas; et al. (Ambio, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

A Perspective on the Clinical Translation of Scaffolds for Tissue Engineering - Matthew J. Webber; Omar F. Khan; Stefanie A. Sydlik; Benjamin C. Tang; Robert Langer (Annals of Biomedical Engineering, 2015)

Chromosomal organizations of major repeat families on potato (Solanum tuberosum) and further exploring in its sequenced genome - Xiaomin Tang; Erwin Datema; Myriam Olortegui Guzman; Jan M. de Boer; Herman J. van Eck; Christian W. B. Bachem; Richard G. F. Visser; Hans de Jong (Molecular Genetics and Genomics, 2014)

Asymmetric sensitivity of first flowering date to warming and cooling in alpine plants - S. P. Wang; F. D. Meng; J. C. Duan; Y. F. Wang; X. Y. Cui; S. L. Piao; H. S. Niu; G. P. Xu; C. Y. Luo; Z. H. Zhang; X. X. Zhu; M. G. Shen; et al. (Ecology, 2014)
Understanding how flowering phenology responds to warming and cooling (i.e., symmetric or asymmetric response) is needed to predict the response of flowering phenology to future climate change that will happen with the occurrence of warm and cold years superimposed upon a long‐term trend. A three‐year reciprocal translocation experiment was performed along an elevation gradient from 3200 m to 3800 m in the Tibetan Plateau for six alpine plants. Transplanting to lower elevation (warming) advanced the first flowering date (FFD) and transplanting to higher elevation (cooling) had the opposite effect. The FFD of early spring flowering plants (ESF) was four times less sensitive to warming than to cooling (by −2.1 d/°C and 8.4 d/°C, respectively), while midsummer flowering plants (MSF) were about twice as sensitive to warming than to cooling (−8.0 d/°C and 4.9 d/°C, respectively). Compared with pooled warming and cooling data, warming alone significantly underpredicted 3.1 d/°C for ESF and overestimated 1.7 d/°C for MSF. These results suggest that future empirical and experimental studies should consider nonlinear temperature responses that can cause such warming–cooling asymmetries as well as differing life strategies (ESF vs. MSF) among plant species.

Identification and molecular characterization of two begomoviruses from Pouzolzia zeylanica (L.) Benn. exhibiting yellow mosaic symptoms in adjacent regions of China and Vietnam - Y. F. Tang; Z. G. Du; Z. F. He; Judith K. Brown; X. M. She (Archives of Virology, 2014)

Linking continental deep subduction with destruction of a cratonic margin: strongly reworked North China SCLM intruded in the Triassic Sulu UHP belt - J. P. Zheng; H. Y. Tang; Q. Xiong; W. L. Griffin; S. Y. O’Reilly; N. Pearson; J. H. Zhao; Y. B. Wu; J. F. Zhang; Y. S. Liu (Contributions to Mineralogy and Petrology, 2014)

Progressive loss of striatal dopamine terminals in MPTP-induced acute parkinsonism in cynomolgus monkeys using vesicular monoamine transporter type 2 PET imaging ([18F]AV-133) - Yajing Liu; Feng Yue; Rongping Tang; Guoxian Tao; Xiaomei Pan; Lin Zhu; Hank F. Kung; Piu Chan (Neuroscience Bulletin, 2014)

Vitamin D supplementation does not improve human skeletal muscle contractile properties in insufficient young males - Daniel J. Owens; Daniel Webber; Samuel G. Impey; Jonathan Tang; Timothy F. Donovan; William D. Fraser; James P. Morton; Graeme L. Close (European Journal of Applied Physiology, 2014)

Safety of combination therapy with milrinone and esmolol for heart protection during percutaneous coronary intervention in acute myocardial infarction - Kian-Keong Poh; Xin Xu; Mark Y. Chan; Chi-Hang Lee; Edgar L. Tay; Adrian F. Low; Koo Hui Chan; Winnie Sia; Liang-Qiu Tang; Huay Cheem Tan; Charles Y. Lui; Vincent Nguyen; et al. (European Journal of Clinical Pharmacology, 2014)

The Dynamic Evaluation of Rock Slope Stability Considering the Effects of Microseismic Damage - N. W. Xu; F. Dai; Z. Z. Liang; Z. Zhou; C. Sha; C. A. Tang (Rock Mechanics and Rock Engineering, 2014)

Using Bayesian optimization method and FLEXPART tracer model to evaluate CO emission in East China in springtime - X. L. Pan; Y. Kanaya; Z. F. Wang; X. Tang; M. Takigawa; P. Pakpong; F. Taketani; H. Akimoto (Environmental Science and Pollution Research, 2014)

Paradox reconsidered: Methane oversaturation in well‐oxygenated lake waters - Kam W. Tang; Daniel F. McGinnis; Katharina Frindte; Volker Brüchert; Hans-Peter Grossart (Limnology and Oceanography, 2014)
The widely reported paradox of methane oversaturation in oxygenated water challenges the prevailing paradigm that microbial methanogenesis only occurs under anoxic conditions. Using a combination of field sampling, incubation experiments, and modeling, we show that the recurring mid‐water methane peak in Lake Stechlin, northeast Germany, was not dependent on methane input from the littoral zone or bottom sediment or on the presence of known micro‐anoxic zones. The methane peak repeatedly overlapped with oxygen oversaturation in the seasonal thermocline. Incubation experiments and isotope analysis indicated active methane production, which was likely linked to photosynthesis and/or nitrogen fixation within the oxygenated water, whereas lessening of methane oxidation by light allowed accumulation of methane in the oxygen‐rich upper layer. Estimated methane efflux from the surface water was up to 5 mmol m −2 d −1 . Mid‐water methane oversaturation was also observed in nine other lakes that collectively showed a strongly negative gradient of methane concentration within 0–20% dissolved oxygen (DO) in the bottom water, and a positive gradient within ≥ 20% DO in the upper water column. Further investigation into the responsible organisms and biochemical pathways will help improve our understanding of the global methane cycle.

Wild-type rabies virus phosphoprotein is associated with viral sensitivity to type I interferon treatment - Xuefeng Niu; Lijun Tang; Tesfai Tseggai; Yi Guo; Zhen F. Fu (Archives of Virology, 2013)

Evaluation of summer temperature and precipitation predictions from NCEP CFSv2 retrospective forecast over China - Lifeng Luo; Wei Tang; Zhaohui Lin; Eric F. Wood (Climate Dynamics, 2013)

Spatial memory and animal movement - William F. Fagan; Mark A. Lewis; Marie Auger‐Méthé; Tal Avgar; Simon Benhamou; Greg Breed; Lara LaDage; Ulrike E. Schlägel; Wen‐wu Tang; Yannis P. Papastamatiou; James Forester; Thomas Mueller (Ecology Letters, 2013)
Memory is critical to understanding animal movement but has proven challenging to study. Advances in animal tracking technology, theoretical movement models and cognitive sciences have facilitated research in each of these fields, but also created a need for synthetic examination of the linkages between memory and animal movement. Here, we draw together research from several disciplines to understand the relationship between animal memory and movement processes. First, we frame the problem in terms of the characteristics, costs and benefits of memory as outlined in psychology and neuroscience. Next, we provide an overview of the theories and conceptual frameworks that have emerged from behavioural ecology and animal cognition. Third, we turn to movement ecology and summarise recent, rapid developments in the types and quantities of available movement data, and in the statistical measures applicable to such data. Fourth, we discuss the advantages and interrelationships of diverse modelling approaches that have been used to explore the memory–movement interface. Finally, we outline key research challenges for the memory and movement communities, focusing on data needs and mathematical and computational challenges. We conclude with a roadmap for future work in this area, outlining axes along which focused research should yield rapid progress.

QTL analysis of the spring wheat “Chapio” identifies stable stripe rust resistance despite inter-continental genotype × environment interactions - E.-N. Yang; G. M. Rosewarne; S. A. Herrera-Foessel; J. Huerta-Espino; Z.-X. Tang; C.-F. Sun; Z.-L. Ren; R. P. Singh (Theoretical and Applied Genetics, 2013)

Molecular characterization of a novel monopartite begomovirus isolated from Pouzolzia zeylanica in China - Y. F. Tang; Z. G. Du; Z. F. He; X. M. She; J. H. Cai (Archives of Virology, 2013)

Levels, seasonal variations, and health risks assessment of ambient air pollutants in the residential areas - W. C. Zhao; J. P. Cheng; Z. Y. Yu; Q. L. Tang; F. Cheng; Y. W. Yin; W. H. Wang (International Journal of Environmental Science and Technology, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Erratum to: Developing a Restorable Wetland Index for Rainwater Basin Wetlands in South-Central Nebraska: A Multi-Criteria Spatial Analysis - Zhenghong Tang; Xu Li; Nan Zhao; Ruopu Li; F. Edwin Harvey (Wetlands, 2012)

Developing a Restorable Wetland Index for Rainwater Basin Wetlands in South-Central Nebraska: A Multi-Criteria Spatial Analysis - Zhenghong Tang; Xu Li; Nan Zhao; Ruopu Li; Edwin F. Harvey (Wetlands, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Mycobacterial infections in adult patients with hematological malignancy - C.-Y. Chen; W.-H. Sheng; C.-C. Lai; C.-H. Liao; Y.-T. Huang; W. Tsay; S.-Y. Huang; J.-L. Tang; H.-F. Tien; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Catastrophic debris flows triggered by a 14 August 2010 rainfall at the epicenter of the Wenchuan earthquake - Chuan Tang; Jing Zhu; Jun Ding; Xiaofei F. Cui; Lei Chen; Jianshi S. Zhang (Landslides, 2011)

In Vitro Toxicity Evaluation of 25-nm Anatase TiO2 Nanoparticles in Immortalized Keratinocyte Cells - Jin Chan; Tang Ying; Yang F. Guang; Li X. Lin; Tang Kai; Zhang Y. Fang; Ye X. Ting; Lin F. Xing; Yang Y. Ji (Biological Trace Element Research, 2011)

Enhanced Fluorescence Anisotropy Assay for Human Cardiac Troponin I and T Detection - Yanling Qiao; Hongmin Tang; Gerhard R. Munske; Prashanta Dutta; Cornelius F. Ivory; Wen-Ji Dong (Journal of Fluorescence, 2011)

Linkage analysis of plasma dopamine β-hydroxylase activity in families of patients with schizophrenia - Joseph F. Cubells; Xiangqing Sun; Wenbiao Li; Robert W. Bonsall; John A. McGrath; Dimitri Avramopoulos; Virginia K. Lasseter; Paula S. Wolyniec; Yi-Lang Tang; Kristina Mercer; Ann E. Pulver; Robert C. Elston (Human Genetics, 2011)

Mechanisms of chloride in cardiomyocyte anoxia-reoxygenation injury: the involvement of oxidative stress and NF-kappaB activation - D. Liu; H. He; G. L. Li; J. Chen; D. Yin; Z. P. Liao; L. Tang; Q. R. Huang; Z. F. Lai; M. He (Molecular and Cellular Biochemistry, 2011)

Occurrence of toxigenic fungi in ochratoxin A contaminated liquorice root - A.J. Chen; L.F. Huang; L.Z. Wang; D. Tang; F. Cai; W.W. Gao (Food Additives & Contaminants: Part A, 2011)

Selection of species resistant to the wood rot fungus Phellinus noxius - J. Wu; S. L. Peng; H. B. Zhao; M. H. Tang; F. R. Li; B. M. Chen (European Journal of Plant Pathology, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

A novel de novo BRCA1 mutation in a Chinese woman with early onset breast cancer - Ava Kwong; Enders K. O. Ng; Edmund Y. H. Tang; Chris L. P. Wong; Fian B. F. Law; Candy P. H. Leung; Aaron Chan; M. T. Cheung; M. Y. To; Edmond S. K. Ma; Dee W. West; James M. Ford (Familial Cancer, 2011)

The effect of dichloroacetate on health- and lifespan in C. elegans - S. Schaffer; J. Gruber; L. F. Ng; S. Fong; Y. T. Wong; S. Y. Tang; B. Halliwell (Biogerontology, 2011)

Downy mildew (Pl 8 and Pl 14 ) and rust (R Adv ) resistance genes reside in close proximity to tandemly duplicated clusters of non-TIR-like NBS-LRR-encoding genes on sunflower chromosomes 1 and 13 - Eleni Bachlava; Osman E. Radwan; Gustavo Abratti; Shunxue Tang; Wenxiang Gao; Adam F. Heesacker; Maria E. Bazzalo; Andres Zambelli; Alberto J. Leon; Steven J. Knapp (Theoretical and Applied Genetics, 2011)

Genetic association analysis highlights new loci that modulate hematological trait variation in Caucasians and African Americans - Ken Sin Lo; James G. Wilson; Leslie A. Lange; Aaron R. Folsom; Geneviève Galarneau; Santhi K. Ganesh; Struan F. A. Grant; Brendan J. Keating; Steven A. McCarroll; Emile R. Mohler III; Christopher J. O’Donnell; Walter Palmas; et al. (Human Genetics, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Estimating the water budget of major US river basins via remote sensing - Huilin Gao; Qiuhong Tang; Craig R. Ferguson; Eric F. Wood; Dennis P. Lettenmaier (International Journal of Remote Sensing, 2010)

A real‐time PCR for the detection of hepatopancreatic parvovirus (HPV) of penaeid shrimp - D C Yan; K F J Tang; D V Lightner (Journal of Fish Diseases, 2010)
Hepatopancreatic parvovirus (HPV) causes a common shrimp disease that occurs in many shrimp farming regions, especially in the Indo Pacific, and infects most of the cultured penaeid species. There are seven geographic HPV isolates known, so a method to detect different HPV types is needed. We developed a sensitive and generic real‐time PCR assay for the detection of HPV. A pair of primers and TaqMan probe based on an HPV sequence obtained from samples of Fenneropenaeus chinensis from Korea were selected, and they were used to amplify a 92 bp DNA fragment. This real‐time PCR was found to be specific to HPV and did not react with other shrimp viruses. A plasmid (pHPV‐2) containing the target HPV sequence was constructed and used for determination of the sensitivity of this assay. The assay could detect a single copy of plasmid DNA, and it was used successfully in finding HPV in shrimp samples from the China‐Yellow Sea region, Taiwan, Korea, Thailand, Madagascar, New Caledonia and Tanzania.

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

The transcription factor GATA-2 does not associate with angiographic coronary artery disease in the Ottawa Heart Genomics and Cleveland Clinic GeneBank Studies - Sonny Dandona; Li Chen; Meng Fan; Md Afaque Alam; Olivia Assogba; Melanie Belanger; Kathryn Williams; George A. Wells; W. H. Wilson Tang; Stephen G. Ellis; Stanley L. Hazen; Ruth McPherson; et al. (Human Genetics, 2010)

Diagnosis of Broad bean wilt virus 1 and Verbena latent virus in Tropaeolum majus in New Zealand - F. M. Ochoa-Corona; J. Tang; B. S. M. Lebas; L. Rubio; A. Gera; B. J. R. Alexander (Australasian Plant Pathology, 2010)

Impacts of cascade run-of-river dams on benthic diatoms in the Xiangxi River, China - N. Wu; T. Tang; X. Fu; W. Jiang; F. Li; S. Zhou; Q. Cai; N. Fohrer (Aquatic Sciences, 2010)

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Sequencing the Potato Genome: Outline and First Results to Come from the Elucidation of the Sequence of the World’s Third Most Important Food Crop - Richard G. F. Visser; Christian W. B. Bachem; Jan M. de Boer; Glenn J. Bryan; Swarup K. Chakrabati; Sergio Feingold; Robert Gromadka; Roeland C. H. J. van Ham; Sanwen Huang; Jeanne M. E. Jacobs; Boris Kuznetsov; Paulo E. de Melo; et al. (American Journal of Potato Research, 2009)

Assignment of genetic linkage maps to diploid Solanum tuberosum pachytene chromosomes by BAC-FISH technology - Xiaomin Tang; Jan M. de Boer; Herman J. van Eck; Christian Bachem; Richard G. F. Visser; Hans de Jong (Chromosome Research, 2009)

Recent positive selection of a human androgen receptor/ectodysplasin A2 receptor haplotype and its relationship to male pattern baldness - Axel M. Hillmer; Jan Freudenberg; Sean Myles; Stefan Herms; Kun Tang; David A. Hughes; Felix F. Brockschmidt; Yijun Ruan; Mark Stoneking; Markus M. Nöthen (Human Genetics, 2009)

Comparison of Approaches to Calibrate a Surface Complexation Model for U(VI) Sorption to Weathered Saprolite - F. Zhang; J. C. Parker; S. C. Brooks; Y.-J. Kim; G. Tang; P. M. Jardine; D. B. Watson (Transport in Porous Media, 2009)

Investigation of Impatiens necrotic spot virus outbreaks in New Zealand - D. R. Elliott; B. S. M. Lebas; F. M. Ochoa-Corona; J. Tang; B. J. R. Alexander (Australasian Plant Pathology, 2009)

Investigation of an outbreak of Soil-borne wheat mosaic virus in New Zealand - B. S. M. Lebas; F. M. Ochoa-Corona; D. R. Elliott; J. Tang; A. G. Blouin; O. E. Timudo; S. Ganev; B. J. R. Alexander (Australasian Plant Pathology, 2009)

Genetic analysis of photoperiod sensitivity in a tropical by temperate maize recombinant inbred population using molecular markers - C. L. Wang; F. F. Cheng; Z. H. Sun; J. H. Tang; L. C. Wu; L. X. Ku; Y. H. Chen (Theoretical and Applied Genetics, 2008)

Near‐surface air temperature estimation from ASTER data based on neural network algorithm - K. B. Mao; H. J. Tang; X. F. Wang; Q. B. Zhou; D. L. Wang (International Journal of Remote Sensing, 2008)

Adaptive segmentation of cerebrovascular tree in time-of-flight magnetic resonance angiography - J. T. Hao; M. L. Li; F. L. Tang (Medical & Biological Engineering & Computing, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Floral traits and isolation of three sympatric Aquilegia species in the Qinling Mountains, China - L.-L. Tang; Q. Yu; J.-F. Sun; S.-Q. Huang (Plant Systematics and Evolution, 2007)

Comparison between back propagation neural network and regression models for the estimation of pigment content in rice leaves and panicles using hyperspectral data - L. Chen; J. F. Huang; F. M. Wang; Y. L. Tang (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Pentachlorophenol Residues in Suspended Particulate Matter and Sediments from the Yangtze River Catchment of Wuhan, China - Z. W. Tang; Z. F. Yang; Z. Y. Shen; J. F. Niu (Bulletin of Environmental Contamination and Toxicology, 2007)

Three non-allelic epistatically interacting methyltransferase mutations produce novel tocopherol (vitamin E) profiles in sunflower - Catherine G. Hass; Shunxue Tang; Scott Leonard; Maret G. Traber; Jerry F. Miller; Steven J. Knapp (Theoretical and Applied Genetics, 2006)

Caspase 3, periodically expressed and activated at G2/M transition, is required for nocodazole-induced mitotic checkpoint - S.-L. Hsu; C. -T. R. Yu; S. -C. Yin; M. -J. Tang; A. -C. Tien; Y. -M. Wu; C. -Y. F. Huang (Apoptosis, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

Phosphorus characteristics correlate with soil fertility of albic luvisols - X. Z. Han; C. Tang; C. Y. Song; S. Y. Wang; Y. F. Qiao (Plant and Soil, 2005)

Distribution of Potato spindle tuber viroid in New Zealand glasshouse crops of capsicum and tomato - B. S. M. Lebas; G. R. G. Clover; F. M. Ochoa-Corona; D. R. Elliott; Z. Tang; B. J. R. Alexander (Australasian Plant Pathology, 2005)

The Fed-1 (CAUU)4 element is a 5? UTR dark-responsive mRNA instability element that functions independently of dark-induced polyribosome dissociation - Sumana Bhat; Li Tang; Angela D. Krueger; Christopher L. Smith; Sharon R. Ford; Lynn F. Dickey; Marie E. Petracek (Plant Molecular Biology, 2004)

Environmental epidemiological study and estimation of benchmark dose for renal dysfunction in a cadmium-polluted area in China - Taiyi Jin; Xunwei Wu; Yinqi Tang; Monica Nordberg; Alfred Bernard; Tingting Ye; Qinhu Kong; Nils-Göoran Lundström; Gunnar F. Nordberg (BioMetals, 2004)

All Roads Lead to Arginine: The Squid Protamine Gene - John D. Lewis; Miriam E. de Jong; Sabira M. Bagha; Alpina Tang; William F. Gilly; Juan Ausió (Journal of Molecular Evolution, 2004)

Lymphocyte surge as a marker for immunorestitution disease due to Pneumocystis jiroveci pneumonia in HIV-negative immunosuppressed hosts - V. C. C. Cheng; I. F. N. Hung; A. K. L. Wu; B. S. F. Tang; C. M. Chu; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

One hundred and one new microsatellite loci derived from ESTs (EST-SSRs) in bread wheat - L. F. Gao; R. L. Jing; N. X. Huo; Y. Li; X. P. Li; R. H. Zhou; X. P. Chang; J. F. Tang; Z. Y. Ma; J. Z. Jia (Theoretical and Applied Genetics, 2004)

Root-induced acidification and excess cation uptake by N2-fixing Lupinus albus grown in phosphorus-deficient soil - J. Shen; C. Tang; Z. Rengel; F. Zhang (Plant and Soil, 2004)

Evaluation of an Immortalized Retinal Endothelial Cell Line as an In Vitro Model for Drug Transport Studies Across the Blood-Retinal Barrier - Jie Shen; Stacy T. Cross; Diane D. S. Tang-Liu; Devin F. Welty (Pharmaceutical Research, 2003)

Recruitment, sustainable yield and possible ecological consequences of the sharp decline of the anchovy ( Engraulis japonicus ) stock in the Yellow Sea in the 1990s - X. Zhao; J. Hamre; F. Li; X. Jin; Q. Tang (Fisheries Oceanography, 2003)
Natural mortality, stock–recruitment relationship and sustainable yield of the anchovy ( Engraulis japonicus ) stock in the Yellow Sea were estimated based on acoustic assessments of the wintering anchovy stock from 1987 to 2002. The stock‐recruitment relationship was estimated to be: R = 151.1 × SSB × e −0.299·SSB , where R is given in billion fish and SSB is in million tons. The optimum sustainable yield of anchovy was estimated at 520 000 tons for the period 1987–2002. The ecological consequences of the sharp decline of the anchovy stock observed after 1996 were examined in terms of the reduction in biomass production in the Yellow Sea ecosystem, as well as the consequences of such reduction on predator–prey interactions and species competition.

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Orthogonal polynomial models to describe yield response of rice to nitrogen and phosphorus at different levels of soil fertility - F. Zhang; J. Shen; R. Li; Z. Rengel; C. Tang (Nutrient Cycling in Agroecosystems, 2003)

Role of phosphorus nutrition in development of cluster roots and release of carboxylates in soil-grown Lupinus albus - J. Shen; Z. Rengel; C. Tang; F. Zhang (Plant and Soil, 2003)

Erratum to: Building a mouse model hallmarking the congenital human cytomegalovirus infection in central nervous system - J. L. Tang; M. L. Wang; J. J. Qiu; D. Wu; W. Hu; B. F. Shi; Y. Hu; J. P. Li (Archives of Virology, 2002)

The inherent cellular level of reactive oxygen species: One of the mechanisms determining apoptotic susceptibility of leukemic cells to arsenic trioxide - J. Yi; F. Gao; G. Shi; H. Li; Z. Wang; X. Shi; X. Tang (Apoptosis, 2002)

Impact of nitrogen form on iron uptake and distribution in maize seedlings in solution culture - C. Zou; J. Shen; F. Zhang; S. Guo; Z. Rengel; C. Tang (Plant and Soil, 2001)

In vitro flowering of bitter melon - S. Wang; L. Tang; F. Chen (Plant Cell Reports, 2001)

Chronic intracerebroventricular exposure to β-amyloid(1-40) impairs object recognition but does not affect spontaneous locomotor activity or sensorimotor gating in the rat - S. Nag; F. Tang; B.K. Yee (Experimental Brain Research, 2001)

Carbon fixation by phytoplankton in high Arctic lakes: Implications of low temperature for photosynthesis - Stiig Markager; Warwick F. Vincent; Evonne P.Y. Tang (Limnology and Oceanography, 1999)
Photosynthesis vs. irradiance relationships were determined for phytoplankton communities from seven lakes in the Canadian high Arctic, including ultraoligotrophic Char Lake, nutrient‐enriched Meretta Lake, and two meromictic lakes. The derived photosynthetic parameters were low for all samples, with a mean (±SD) light‐saturated photosynthetic rate (P m B ) of 0.46 (±0.28) g C g −1 chlorophyll a (Chl a )h −1 and a mean α B (light‐limitation parameter) of 1.23 (±0.56) g C g −1 Chl a m 2 mol −1 . The saturation irradiance (E Κ ) ranged from 50 to 196 μmol quanta m −2 s −1 and was positively correlated with mean irradiance for the water column. Quantum yields for photosynthesis in the Arctic lake phytoplankton were also low (mostly −1 quanta). An intersystem comparison of α B and P m B values with literature data for algae from other cold environments showed that the photosynthetic parameters for phytoplankton in Arctic and Antarctic lakes are three‐ to sixfold lower than for marine algae, ice algae, and cultures over the same low‐temperature range. This may be the result of more severe nutrient stress in high latitude lakes relative to polar marine environments and to the persistence of nonactive pigments in cold freshwaters.

Lorazepam for chronic catatonia: a randomized, double-blind, placebo-controlled cross-over study - G. S. Ungvari; Helen F. K. Chiu; Lok Yee Chow; Benjamin S. T. Lau; Wai Kwong Tang (Psychopharmacology, 1999)

Synthesis and diversity analysis of lead discovery piperazine-2-carboxamide libraries - Timothy F. Herpin; George C. Morton; Allison K. Dunn; Cedric Fillon; Paul R. Menard; Sheng Yu Tang; Joseph M. Salvino; Richard F. Labaudinière (Molecular Diversity, 1998)

Identification and genetic characterization of yeasts isolated from freshwater prawns, Macrobrachium rosenbergii de Man, in Taiwan - C C Lu; K F J Tang; S N Chen (Journal of Fish Diseases, 1998)
Since 1987, farmers in southern Taiwan have reported significant disease‐related mortalities in freshwater prawns. Most mortalities have occurred during the winter, and usually almost all the adult prawns die within 4–5 days after clinical signs appear. Histopathological studies show that cells in hepatopancreatic ducts and tubules are vacuolized and degenerated. Large numbers of membrane‐bound yeast aggregates are observed in the affected tissues. Two hundred and seventeen yeast isolates were obtained from diseased prawns, pond water and sediments from six areas. DNA restriction fragment length polymorphism (RFLP) was used to analyse the yeast genomes and to categorize them into five groups. Conventional biochemical and metabolic methods were then used to identify the yeasts of each group. The results showed that two strains of Candida sake (I and II), Pichia anomala, Endomyces fibuliger and Candida famata were present. In addition, the RAPD (random amplified polymorphic DNA) method was used to determine their genomic similarities. Two strains (I and II) of C. sake were the most similar (72%). C. sake I appears to be the primary causative agent of disease, based on frequencies of occurrence of the yeasts found in the diseased prawns.

Plant regeneration through organogenesis from callus induced from mature zygotic embryos of loblolly pine - W. Tang; F. Ouyang; Z. Guo (Plant Cell Reports, 1998)

Intranigral ventral mesencephalic grafts and nigrostriatal injections of glial cell line-derived neurotrophic factor restore dopamine release in the striatum of 6-hydroxydopamine-lesioned rats - F. I. Tang; L. T. Tien; F. C. Zhou; B. J. Hoffer; Y. Wang (Experimental Brain Research, 1998)

Control of reactive balance adjustments in perturbed human walking: roles of proximal and distal postural muscle activity - P.-F. Tang; Marjorie H. Woollacott; Raymond K. Y. Chong (Experimental Brain Research, 1998)

Geochemistry of HCO3 − at the sediment-water interface of lakes from the Southwestern Chinese plateau - F. C. Wu; H. R. Qing; G. J. Wan; D. G. Tang; R. G. Huang; Y. R. Cal (Water, Air, & Soil Pollution, 1997)

Light and electron microscopic evidence of white spot disease in the giant tiger shrimp, Penaeus monodon (Fabricius), and the kuruma shrimp, Penaeus japonicus (Bate), cultured in Taiwan - C S Wang; K F J Tang; G H Kou; S N Chen (Journal of Fish Diseases, 1997)
Since 1992, mass mortalities among cultured giant tiger shrimp, Penaeus monodon (Fabricius), and kuruma shrimp, Penaeus japonicus (Bate), have been observed in Taiwan. The condition is known as ‘white spot disease’ (WSD), based on the characteristic white spots on the cuticle of diseased shrimp. With the scanning electron microscope, two sizes of white spots were observed. Each spot represented a protrusion on the inside surface of the carapace. The composition of white spots was similar to that of the cuticule, most calcium, as determined with an energy dispersive spectrometer. Histological studies of moribund, infected specimens revealed degenerated cells, characterized by hypertrophied nuclei, in various meso‐ and ectodermal tissues. Infected tissues included cuticular epidermis, connective tissue, lymphoid organ, antennal gland, and haematopoietic, gill and nervous tissue. Nuclei were Feulgen‐positive and no occlusion body was found in the necrotic tissue. Transmission electron microscopy revealed the presence of rod‐shaped and enveloped virions in the hypertrophied nuclei. The virions measured 298 ± 21 × 107 ± 8 nm in the giant tiger shrimp and 248 ± 12 × 104 ± 8 nm in the kuruma shrimp. In an experimental infection trial, cumulative mortality was 40% within 14 days under stress conditions. No mortality was observed in controls or in non‐stressed infected shrimp. Experimental infections show that environmental stressors such as ammonia may enhance the severity of WSD virus infections in cultured shrimp.

Polar cyanobacteria versus green algae for tertiary waste-water treatment in cool climates - Evonne P. Y. Tang; Warwick F. Vincent; Daniel Proulx; Paul Lessard; Joël de la Noüe (Journal of Applied Phycology, 1997)

Anxiolytic-like effects of PNU-101017, a partial agonist at the benzodiazepine receptor - A. H. Tang; S. R. Franklin; D. B. Carter; V. H. Sethy; L. M. Needham; E. J. Jacobsen; P. F. Von Voigtlander (Psychopharmacology, 1997)

Forecasting the equatorial Pacific sea surface temperatures by neural network models - F. T. Tangang; W. W. Hsieh; B. Tang (Climate Dynamics, 1997)

Air Pollution in Singapore: Its Multielemental Aspect as Measured by Nuclear Analytical Techniques - I. Orlić; Bao Wenlan; F. Watt; S.M. Tang (Environmental Monitoring and Assessment, 1997)

Protein binding, sister chromatid exchange and expression of oncogene proteins in patients treated with cisplatinum (cisDDP)-based chemotherapy - F. Perera; H. K. Fischman; K. Hemminki; P. Brandt-Rauf; H. L. Niman; S. Smith; E. Toporoff; K. O'Dowd; M. X. Tang; W. Y. Tsai; M. Stoopler (Archives of Toxicology, 1990)

Factors affecting pathogenicity of NPV preparations to the corn earworm,Heliothis armigera - S. J. Tuan; L. C. Tang; R. F. Hou (BioControl, 1989)